2021
DOI: 10.1016/j.jns.2021.119841
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric transverse myelitis during COVID-19 asymptomatic infection: A case report

Abstract: pathogenesis. Clinical heterogeneity and confounding factors also impair the search for alternative mechanisms. Therefore, we studied the CSF of 13 patients with neurological symptoms during the acute phase of their hospitalization, looking for clues suggesting a specific dysimmune phenomenon. MethodsCSF underwent conventional analysis and RT-PCR for SARS-CoV-2; a in-house HEK293 cell-based assay was also arranged to identify anti-spike antibodies. Albumin ratio, IgG index and oligoclonal bands were also asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Despite minor improvement, it was deemed necessary for him to undergo gastrostomy and tracheostomy (16). Grasso et al reported the case of a 12-year-old boy with an asymptomatic COVID-19 infection (17). The patient complained of nuchal pain followed by hypoesthesia on the right hemisoma that persisted for twelve hours.…”
Section: Discussionmentioning
confidence: 99%
“…Despite minor improvement, it was deemed necessary for him to undergo gastrostomy and tracheostomy (16). Grasso et al reported the case of a 12-year-old boy with an asymptomatic COVID-19 infection (17). The patient complained of nuchal pain followed by hypoesthesia on the right hemisoma that persisted for twelve hours.…”
Section: Discussionmentioning
confidence: 99%